The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1155/2019/3821025
|View full text |Cite
|
Sign up to set email alerts
|

A Fast Multiobjective Fuzzy Clustering with Multimeasures Combination

Abstract: Most of the existing clustering algorithms are often based on Euclidean distance measure. However, only using Euclidean distance measure may not be sufficient enough to partition a dataset with different structures. Thus, it is necessary to combine multiple distance measures into clustering. However, the weights for different distance measures are hard to set. Accordingly, it appears natural to keep multiple distance measures separately and to optimize them simultaneously by applying a multiobjective optimizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 41 publications
(63 reference statements)
0
7
0
Order By: Relevance
“…Recent research has reported some first steps towards exploiting the intrinsic multi-criterion nature of MvC [14,11,15,16,17,8]. In MvC, data views are available either in the form of multiple feature sets or as multiple dissimilarity matrices [5,6,18].…”
Section: Multiview Data Clusteringmentioning
confidence: 99%
“…Recent research has reported some first steps towards exploiting the intrinsic multi-criterion nature of MvC [14,11,15,16,17,8]. In MvC, data views are available either in the form of multiple feature sets or as multiple dissimilarity matrices [5,6,18].…”
Section: Multiview Data Clusteringmentioning
confidence: 99%
“…Clustering is used to divide a set of objects, where objects in the same group are more similar to each other than to objects in different groups. Fuzzy C-means (FCM) [29] is one of the most popular clustering algorithms and is based on the fuzzy set principle. FCM evolves a partition matrix U (X ) during computation and minimizes equation (1).…”
Section: Problem Statement a Cluster Analysismentioning
confidence: 99%
“…We compared the proposed method with three classic singleobjective clustering algorithms (i.e., the differential evolution algorithm (DE) [40], particle swarm optimization (PSO) [41], and FCM [29]) on 8 UCI data sets. As seen in Table 4, the F − measure values of DE, PSO and FCM are all lower than that of HCHPS-MOEC.…”
Section: E Ablation Study 1) Evaluation On the Impact Of Multiobjective Optimizationmentioning
confidence: 99%
“…However, modelling the actual traffic behavior accurately is difficult, and optimization algorithms based on the aforementioned model may be ineffective. Some dynamic programming algorithms with a large amount of calculation are unsuitable for real-time control [9]. Fuzzy control does not need accurate modelling, and the design of a fuzzy controller is relatively simple.…”
Section: Introductionmentioning
confidence: 99%